2020 annual report on education spending in England - Jack Britton; Christine Farquharson; Luke Sibieta; Imran Tahir; Ben Waltmann (Institute for Fiscal Studies (IFS), 2020)
In our annual series of reports on education spending, funded by the Nuffield Foundation, we bring together data on education spending per student across the life cycle and provide analysis about the major issues facing different sectors. In this year's report for 2020, we update our estimates of spending per student and analyse the challenges facing each phase of education due to the ongoing COVID-19 pandemic. We focus on the medium-term challenges facing providers as they respond to substantial changes in student numbers, as well as the loss of learning and increased inequalities that are likely to have emerged during lockdown. The challenges facing each sector will be very different and our analysis partly draws on special reports we have already published looking at the financial challenges facing the early years and higher education sectors. As our special report on the early years makes clear, the main challenge facing the early years is simply remaining open as parental demand remains well below pre-pandemic levels. The widespread closure of settings would represent a significant economic and social cost, particularly if closures are concentrated in certain areas of the country. Evidence suggests that the closure of schools to most pupils during lockdown has led not only to a significant loss of learning but also to a widening of existing educational inequalities. Mitigating these effects will be a major challenge facing the school sector over the next few years. Further education colleges and sixth forms will also face challenges around education catch-up, but may also need to expand to accommodate extra students as apprenticeship and employment opportunities dry up. As our special report on higher education demonstrates, higher education institutions are heavily exposed to financial losses as a result of pension scheme losses, declines in international student numbers and changes in domestic student participation. These calculations are updated in this annual report.
Keywords: 330